STUDIES ON EFFECT OF SPACING AND NITROGEN ON FALSE FLAX (CAMELINA SATIVA CV CALENA) UNDER CENTRAL-WESTERN HIMALAYAS OF INDIA - ANUJA KUMARI,; P. K. JOSHI,; MOHD.MOHSIN,; M. C. ARYA,; Z. AHMED, (The Bioscan, 2015)
False flax [Camelina sativa (L.) Crantz.] popularly known as Gold-of pleasure a proposed biofuel species is an oil seed crop of Brassicacea family introduced in India in 2009. An experiment was conducted during 2011-13 at Defence Institute of Bio-Energy Research, Field Station- Pithoragarh, Uttarakhand, India to investigate the effect of spacing and nitrogen fertilization on C sativa cv Calena for the large scale multiplication and production of seed for biofuel purpose. Field trials were designed in Split plot arrangement based on Randomized Complete Block Design with three replications. Main plots were spacing (RXP) including 30X10 and 30X15cm and subplots were nitrogen (Urea, 46% nitrogen) including zero, 30, 60, 90 and 120kg/ha. Results showed that different levels of spacing had significant (P<0.05) effect on flowering and pod formation (days), branch/plant, plant height, pods/plant, seed as well as oil yield except oil content per centage. The addition of nitrogen fertilizer had significant effects on all the studied growth and yield parameters of Camelina. Statistical interpretation at P<0.05 reveals, the maximum seeds/pod (12.00 No), pods/plant (152.00 No), seed yield (910.47kg/ha), oil content (36.10%) and oil yield (369.303lit/ha) were noticed for the crop with spacing of 30X15cm along with the N fertilization of 30kg/ha. This study suggests that optimum spacing as well N- fertilization increase the productivity of Camelina as emerging biofuel crop.